New Economy or Leveraged Hype? - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2002)
The U.S. stock market is driven more by mergers and acquisitions than by the so-called "real economy." Until another merger boom develops, don't expect a new bull market.
Keywords: 330; acquisition; corporation; finance; market; merger; M&A; stock; US; United States